MicroRNAs Classify Different Disease Behavior Phenotypes of Crohn's Disease and May Have Prognostic Utility. Issue 9 (September 2015) - Peck, Bailey C. E.; Weiser, Matthew; Lee, Saangyoung E.; Gipson, Gregory R.; Iyer, Vishal B.; Sartor, Ryan B.; Herfarth, Hans H.; Long, Millie D.; Hansen, Jonathan J.; Isaacs, Kim L.; Trembath, Dimitri G.; Rahbar, Reza; et al.
Abstract : Background: There is a dire need for reliable prognostic markers that can guide effective therapeutic intervention in Crohn's disease (CD). We examined whether different phenotypes in CD can be classified based on colonic microRNA (miRNA) expression and whether miRNAs have prognostic utility for CD. Methods: High-throughput sequencing of small and total RNA isolated from colon tissue from patients with CD and controls without Inflammatory Bowel Disease (non-IBD) was performed. To identify miRNAs associated with specific phenotypes of CD, patients were stratified according to disease behavior (nonstricturing, nonpenetrating; stricturing; penetrating), and miRNA profiles in each subset were compared with those of the non-IBD group. Validation assays were performed using quantitative reverse transcription polymerase chain reaction. These miRNAs were further evaluated by quantitative reverse transcriptase polymerase chain reaction on formalin-fixed, paraffin-embedded tissue (index biopsies) of patients with nonpenetrating CD at the time of diagnosis that either retained the nonpenetrating phenotype or progressed to penetrating/fistulizing CD. Results: We found a suite of miRNAs, including miR-31-5p, miR-215, miR-223-3p, miR-196b-5p, and miR-203 that stratify patients with CD according to disease behavior independent of the effect of inflammation. Furthermore, we also demonstrated that expression levels of miR-215 in index biopsies of patients with CD might predict the likelihood of progression to penetrating/fistulizing CD. Finally, using a novel statistical simulation approach applied to colonic RNA-sequencing data for patients with CD and non-IBD controls, we identified miR-31-5p and miR-203 as candidate master regulators of gene expression profiles associated with CD. Conclusions: miRNAs may serve as clinically useful prognostic markers guiding initial therapy and identifying patients who would benefit most from effective intervention. Abstract : Article first published online 6 July 2015.Supplemental Digital Content is Available in the Text.